The Experience of Deviated Reproductive Health Behaviors in Adolescents Based on Theory of Planned Behavior - Lelah Fatimah; Nofa Anggraini (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
The behavior of Indonesian adolescents in free sex freedom from year to year has not decreased, even increasing. Casual sex can increase the rate of unwanted pregnancies and abortions. The purpose of this study was to qualitatively analyze the experience of deviant reproductive health behavior in adolescents based on the theory of planned behavior. This research is a qualitative analysis using the theory of planned behavior approach. This research will be conducted in the lebak wangi area of Serang City in May – June 2023. Data collection was conducted using in-depth interviews and interview guidelines. In testing the validity of the data, researchers use the triangulation method (triangulaton). There are 4 main informants, 2 triangulators, and 4 supporting informants. Results: (1) Background factors that have a role to form behavioral beliefs include beliefs in consensual feelings and mutual desire to have free sex between men and women. (2) Subjective norms are formed because some couples want to follow in the footsteps of friends who have already had free sex or are exposed from people closest to them who do have partners who are not halal to have sex with (cheating). (3) Control belief is the experience of peers or personal experiences of having kissed or had such relationships before.